Rare Case of Post Traumatic Carotico-Juglar-Vertebral Fistula with Pseudo Aneurysm - Kumar, Saurabh; Aga, Pallavi; Srivatstav, P. K.; Dwivedi, Durgesh K.; Parihar, Anit; Kohli, Neera (International Journal of Innovative Research in Medical Science, 2016)
Arteriovenous fistula (AVF) is usually seen after acute vascular injuries. An AVF with pseudo aneurysm may present soon after the vascular injury or later. Since the AVF are associated with direct shunting of blood between artery and vein thus bypassing the capillaries, they are usually associated with significant haemodynamic instability. Uncorrected large AVF lead to significant morbidity and may finally land up in high output cardiac failure in rare cases. Proper diagnosis of AVF needs careful clinical examination and imaging modalities like ultrasound and CT angiography.